2012
DOI: 10.1007/s12262-012-0521-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Duct to Duct biliary Anastomosis the Rule in Orthotopic Liver Transplantation?

Abstract: Biliary complications after Liver Transplantation continue to be the major cause of morbidity in 11-25 % of patients. Biliary complications in patients who underwent orthotopic liver transplantation (OLT) at our institute between March 2007 and June 2010 were analyzed retrospectively. 32 patients underwent Deceased Donor Liver Transplantation (DDLT) and in 12 patients Living Donor Liver Transplantation (LDLT) was done. No patients were lost to follow up. Follow up ranged between 4 and 44 months. During the stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Transection of common hepatic duct or common bile duct can be repaired immediately through a tension-free end-to-end anastomosis with or without an internal stent, using a non-absorbable suture. End-to-end anastomosis with internal stent was associated with a significantly higher stricture rate than choledocho-choledochostomy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transection of common hepatic duct or common bile duct can be repaired immediately through a tension-free end-to-end anastomosis with or without an internal stent, using a non-absorbable suture. End-to-end anastomosis with internal stent was associated with a significantly higher stricture rate than choledocho-choledochostomy [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Roux-en-Y hepaticojejunostomy (RYHJ) is recommended when there is a long tissue loss [ 21 , 22 ]. In BDI, especially in cases treated in early phase (within 45 days), inflammation and adhesion not only can cause slight inaccuracy of injury classification but also hinder the recognition of remnant healthy biliary tract which will be used in biliary-enteric anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…However, our findings of increased intraoperative blood loss in patients developing biliary complications ( P < 0.001) has been reported in a few other studies. 25 , 26 A recent study on a large cohort of liver transplanted children did not see a correlation between intraoperative blood units transfused and the development of biliary complications, 27 suggesting adults might be more sensitive to intraoperative blood loss and development of such complications.…”
Section: Discussionmentioning
confidence: 99%
“…These results are compatible with the study from Selvalkular et al . who reported that increased intraoperative blood loss was a predictor for post‐transplant biliary complications including BAS after LT. The current options to increase platelet counts include platelet transfusion, thrombopoietin mimetic agents, thrombopoietin‐receptor agonists, splenectomy, and ligation of the splenic artery.…”
Section: Discussionmentioning
confidence: 99%